Cota cinerea (Anthemideae, Asteraceae), a distinct new species from Türkiye - Yaşayacak, Hasan; Bani, Bariş; Özbek, Mehmet Ufuk; Sabdani, Mardiya (Phytotaxa, 2025)
This study describes and illustrates Cota cinerea, a new species from Bartın Province, Türkiye. While it shares certain morphological traits with C. tinctoria and C. triumfetti, it is clearly distinguishable based on a unique combination of characters. These include the presence of sterile shoots up to 30 cm, a very dense, greyish-whitish adpressed tomentose indumentum, and consistently 2-pinnatisect leaves. Moreover, C. cinerea exhibits significantly larger middle and upper leaves, broader primary leaf segments, and more robust disc achenes and corona structures than in both related taxa. Differences in achene micromorphology revealed through scanning electron microscopy (SEM) further support its distinctiveness. To assess the phylogenetic placement of the new species within Cota, both Maximum Likelihood and Bayesian Inference analyses were conducted using the nuclear ribosomal ITS region. In addition to morphological and molecular assessments, the study includes distribution maps and an evaluation of its conservation status following IUCN criteria.